Association Between Infant Feeding Practices and First Meaningful Words at First Year of Life: A Prospective Cohort Study of Thai Children1. (March 2015) - Chaimay, Bhunyabhadh; Ruagdaraganon, Nichara; Thinkhamrop, Bandit; Thinkhamrop, Jadsada
Feeding practices show many benefits for child and cognitive development. The objective was to investigate the association between infant feeding practices and the first meaningful words of Thai children. The participants enrolled in this longitudinal study were 4245 children born between July 2000 and June 2002. They resided in 3 rural and 2 urban areas of Thailand and were followed from birth to childhood. The outcome was time from birth to expression of first meaningful words. Outcome and feeding information were gathered using a diary method, with parents and caregivers recording daily development. Nonstatistically significant corresponding reduction in time to expression of first meaningful words was found among children who were breastfed, and this increased with duration of breastfeeding. Breastfeeding may reduce the time taken for expression of first meaningful words by about 2% (hazard ratio = 0.98; 95% confidence interval = 0.94 to 1.01). No association between infant feeding practices and the expression of first meaningful words was found.